David, Once and Future King?: A Closer Look at the Postscript of Psalm 72.20 - Hensley, Adam D. (Journal for the study of the Old Testament, 2021)
How did scribes understand Psalm 72.20, ‘Ended are the prayers of David, son of Jesse’, in view of subsequent Davidic psalms in the MT Psalter? After appraising the major proposals and examining its earliest reception (MT pointing, DSS parallels, and early Jewish and patristic evidence), this paper argues that the oft-overlooked genealogical qualifier ‘ben Jesse’ indicates a primary focus on ‘historical’ David in Books 1–2, whereas Books 3–5 primarily have future or eschatological ‘David’/Davidic monarchy in view. This synchronic account of 72.20’s meaning in the Psalter honours its plainest sense and explains its editorial retention/reuse, yet leaves room for diachronic theories about its origins. It also accounts for evidence other theories do not, especially Psalm 86’s identification as a ‘prayer (תפלה‎) of David’ and the Psalms’ predominant association of תפלה‎ with David. Further implications for ‘psalmic voice’ and David’s significance as YHWH’s praying servant in the Psalter are then explored.